Analysis of Procedure for Determining ATM Rental Rate at KPKNL - Ajeng Kharisma Ayu Ajitama; Andi Asrihapsari (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this study is to determine the methods used, influencing variables, procedures, constraints, and efforts in determining ATM (Automated Teller Machine) rental rates at the State Assets and Auctions Services Office (Indonesian: Kantor Pelayanan Kekayaan Negara dan Lelang, abbreviated KPKNL) Surakarta. This study is qualitative research that used a descriptive method. The data were collected using primary and secondary data. The findings of this study show: (1) the method used in the process of determining ATM rental rates at KPKNL Surakarta using the Market Approach, namely the Market Data Comparison Method and ATM Modeling Techniques, (2) the variables that affect the determination of ATM rental rates consists of transactional and non-transactional variables, (3) the procedure for determining ATM rental rates at KPKNL Surakarta based on the Regulation of the Minister of Finance (Indonesian: Peraturan Menteri Keuangan, abbreviated PMK) Number 173/PMK.06/2020, (4) obstacles experienced in determining ATM rental rates are the difficulty of collecting databases from several National Bank,s (5) efforts made are using field surveys, coordinating with banks, and searching for data via the internet. Based on the results of the study, the researchers advise KPKNL Surakarta to maintain its performance by maximizing the efforts that have been made so that the work is more effective and efficient